The Role of Customer Brand Engagement in Mediating the Effect of Brand Expressiveness and Brand Community Identification on Brand Loyalty - Firda Alvi Damayanti; Dimas Bayu Wicaksono; Muhammad Rivaldi Shadam; Aang Curatman (Universitas KH. Abdul Chalim Mojokerto, 2024)
This study aims to determine the role of Customer Brand Engagement in mediating the effect of Brand Expressiveness and Brand Community Identification on Brand Loyalty. The research used a quantitative research method by distributing questionnaires to 180 consumers in Cirebon City who used an iPhone smartphone. The quantitative data was analyzed using validity tests, reliability tests, R-square tests (R²), and hypothesis tests processed using SEM with Smart PLS 4.0 tool. The results of this study indicate that Brand Expressiveness does not have a positive and significant effect on Customer Brand Engagement. Brand Community Identification has a positive and significant effect on Customer Brand Engagement. Brand Expressiveness has a positive and significant effect on Brand Loyalty. Brand Community Identification has a positive and significant effect on Brand Loyalty. Customer Brand Engagement does not have a positive and significant effect on Brand Loyalty. Customer Brand Engagement does not mediate the effect of Brand Expressiveness on Brand Loyalty. Customer Brand Engagement also does not mediate the effect of Brand Community Identification on Brand Loyalty.